2016
DOI: 10.1002/ange.201602278
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Lithium Boracarbonate Ion Pairs by Copper‐Catalyzed Multi‐Component Coupling of Carbon Dioxide, Diboron, and Aldehydes

Abstract: Abstract:The catalytic selective multi-component coupling of CO 2 ,b is(pinacolato)diboron, LiOtBu, and aw ide range of aldehydes has been achieved for the first time by using an NHC-copper catalyst. This transformation has efficiently afforded as eries of novel lithium cyclic boracarbonate ion pair compounds in high yields from readily available starting materials.This protocol has not only provided anew catalytic process for the utilization of CO 2 ,b ut it has also constituted anovel route for the efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Therefore, the chemo-, regio-, and enantioselective cyanoborylation of allenes still remains a highly attractive research subject for the synthesis of valuable molecules containing multiple synthetically important functional groups, including a chiral nitrile unit, a boryl group, and a CC double bond. During our previous studies on the catalytic addition of copper boryl species to alkynes, 15 aldehydes, 16 and imines, 17 we became interested in the development of selective cyanoborylation of allenes through copper boryl catalysis. Herein, we report a copper-catalyzed chemo-, regio-, and enantioselective cyanoborylation of allenes, which afforded β-boryl allyl nitriles efficiently (Scheme 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the chemo-, regio-, and enantioselective cyanoborylation of allenes still remains a highly attractive research subject for the synthesis of valuable molecules containing multiple synthetically important functional groups, including a chiral nitrile unit, a boryl group, and a CC double bond. During our previous studies on the catalytic addition of copper boryl species to alkynes, 15 aldehydes, 16 and imines, 17 we became interested in the development of selective cyanoborylation of allenes through copper boryl catalysis. Herein, we report a copper-catalyzed chemo-, regio-, and enantioselective cyanoborylation of allenes, which afforded β-boryl allyl nitriles efficiently (Scheme 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Ph 2 I + OTf − 1e was triggered by CO 3 2− to give I, which accelerated radicals 8e and PhI-CO 3 − formed via homo cleavage. The intermediate II formed from vinylboronate 2a and CO 3 2− enabled the addition of radicals 8e to form the C-C bond [45][46][47] , generating the "ate" α-boronate adduct radical species III [48][49][50][51][52] . Species III was capable of occurring SET reaction with radical CO 3 − to give the intermediate moiety IV and intramolecular dehydrocarbonate give the "ate" intermediate VI, which further eliminated to give the desired product 3e.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a comparable selective multicomponent coupling of CO 2 , bis(pinacolato)diboron, LiOt-Bu, and aldehydes to obtain lithium cyclic boracarbonate ion pair compounds has been reported, but an NHC-copper catalyst was required to achieve success. 18 The energetic profile of the reaction with CO 2 was also studied computationally for the borylamine 2 (Figure 5). In the first place, we found that the formation of a hypothetical insertion product of CO 2 into the B−N bond of 2 to form a carbamate compound is an uphill process, with the resulting product being nearly 21 kJ mol −1 above the corresponding starting materials in benzene solution (29 kJ mol −1 in gas phase).…”
Section: ■ Results and Discussionmentioning
confidence: 99%